2003
DOI: 10.3189/172756503781830980
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations in albedo on Storglaciären, Sweden

Abstract: Extensive albedo data from Storglaciären, Sweden, during nine summers are analyzed, focusing on the effect of surface slope on measurements and on the influence of clouds on albedo of both snow and ice surfaces. On clear-sky days, albedo continuously dropped throughout the day by > 0.3 when derived from measurements in a horizontal plane over the slightly sloping surface. When we correct for the tilt effect, over frozen surfaces the apparent decrease in albedo largely disappeared, while over melting surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 48 publications
3
61
0
Order By: Relevance
“…As clouds have been found to significantly augment the albedo at this site (Abermann et al, 2013), and elsewhere (e.g. Jonsell et al, 2003), the negative correlation between albedo and sublimation must partly reflect the effect of clouds, and the lower correlation between sublimation and snowfall (r = −0.22) tends to confirm this. A negative correlation with the east-west component of the wind (u-wind, r = 0.33) implies that sublimation is somewhat enhanced when the wind originates from a more westerly direction.…”
Section: Meteorological Conditions Driving Sublimation Processesmentioning
confidence: 57%
“…As clouds have been found to significantly augment the albedo at this site (Abermann et al, 2013), and elsewhere (e.g. Jonsell et al, 2003), the negative correlation between albedo and sublimation must partly reflect the effect of clouds, and the lower correlation between sublimation and snowfall (r = −0.22) tends to confirm this. A negative correlation with the east-west component of the wind (u-wind, r = 0.33) implies that sublimation is somewhat enhanced when the wind originates from a more westerly direction.…”
Section: Meteorological Conditions Driving Sublimation Processesmentioning
confidence: 57%
“…Brock et al (2000) found no correlation between ice albedo and θ 0 or cloud cover. Jonsell et al (2003) also observed only a very weak albedo change under cloudy skies.…”
Section: Application Ii: Clouds and Albedomentioning
confidence: 95%
“…The daily mean α will be the same regardless of using S i , S d or S c as incoming short-wave flux. Jonsell et al (2003) found only a limited effect of clouds on α during ice conditions, probably because the multiple reflection of radiation will be limited due to lower α. The location of the AWS was snow covered during the period of data collection, with the exception of a few days at the end of the melt season 2006/07, but still with α exceeding 0.55, and therefore we applied Eqs.…”
Section: Correction Of Short-wave Radiation and Albedomentioning
confidence: 99%
“…A high sensitivity of the mass balance to changes in T air for glaciers on the nearby KGI was pointed out by Knap et al (1996) from the results of running a simple ice-flow model forced by an energy-balance model, after perturbating T air , until a new equilibrium state was reached. An energybalance model based on single-point measurements on Ecology glacier, KGI, produced an increase in ablation by 15 % in response to a 1 K temperature increase (Bintanja, 1995).…”
Section: Model Validation and Sensitivity Analysismentioning
confidence: 99%